The ANALISIS PERILAKU ONLINE IMPULSE BUYING DITINJAU DARI FLASH SALE DAN LOCUS OF CONTROL PADA MAHASISWA UNPER KONSUMEN SHOPEE - Elisa Nurchoiriah; Rita Tri Yusnita; Ari Arisman (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2022)
The rise of Online Stores, usually triggers people to be easily tempted to shop, because of conveniences such as saving time and energy, available many promos, and many payment options. This results in many students making planned and unplanned online purchases. This study was conducted to analyze Online Impulse Buying Behavior in terms of Flash Sale and Locus of Control on Shopee Consumer Unper Students. This study used a quantitative method with a survey approach. Data was collected using a questionnaire. The data collected in the form of primary data. Data analysis in this study used the classical assumption test, multiple regression analysis, correlation coefficient analysis, determination coefficient analysis using SPSS software. The results of this study indicate that Simultaneous Flash Sale and Locus of Control have a significant effect on Online Impulse Buying at Shopee, Partial Flash Sale has a significant effect on Online Impulse Buying at Shopee, Partial Locus of Control has no significant effect on Online Impulse Buying at Shopee.